IMPACT OF KNOWLEDGE MANAGEMENT ON BUSINESS PERFORMANCE IMPROVEMENT: A STUDY ON BATIK BUSINESS - Singgih Santoso (SMBJ: Strategic Management Business Journal, 2021)
Entrepreneurial orientation is one of the antecedent variables that can improve small and medium enterprises' performance. This article provides a discussion on the scope of company performance, especially in small and medium enterprises. This article examines and analyzes the effect of entrepreneurial orientation on performance with management knowledge as a moderating variable in Indonesia's small and medium enterprises. The research sample, 45 small and medium batik enterprises in the city of Surakarta, Indonesia. Hypothesis analysis, using SPSS 22.00. The results showed that entrepreneurial orientation dimensions (innovation, proactive, risk-taking) significantly affected enterprise performance with β = .560 and sig ≤ 0.05. However, knowledge management does not influence moderation, where the effect is on performance with β = -.220 and sig > .112.